Prior use of antibiotics and clinical characteristics of women who developed urinary tract infection due to beta-lactamase bacteria in a peruvian hospital: Uso previo de antibióticos y características clínicas de mujeres que desarrollaron infección urinaria por bacterias productoras de Betalactamasas en un hospital peruano - Valero Román, Ítalo Renato (2021)
Introduction: The overused of antibiotics has existed as a threat to public health for several years. The World Health Organization (WHO) warns that in the year 2050 the "post-antibiotic era" will begin, where approximately 10 million deaths per year will be attributed to resistant infections. The infection where this type of bacteria is most relevant is in urinary tract pathology. Objective: Determine the factors associated with the development of urinary tract infections by beta-lactamase-producing bacteria in older adults in the internal medicine service of the Dos de Mayo National Hospital. Methods: An analytical, cross-sectional, retrospective, case-control type study was carried out. Data were obtained through the review of medical records, with the completion of a data collection form related to sociodemographic aspects such as clinical data. With a total sample of 139 patients, 56 cases and 86 controls were obtained. To measure the association, we used the Odds Ratio, the statistical software SPSS was used. Results: A statistically significant association was observed between E. Coli ESBL infection with antecedents such as previous use of antibiotics and a history of recurrent urinary infection. The ORs and the confidence intervals of the variables that were shown to be significant were: recurrent urinary tract infection (95% CI, OR = 1,722), Anemia (95% CI OR = 1.96), Hypothyroidism (95% CI, OR = 1.13), Hypertension (95% CI, OR = 1,050), multi-pregnancy (95% CI, OR = 1,062) and History of previous antibiotic use (95% CI, OR = 22,106). Conclusion: The study identified the average age of presentation of urinary infection by E. Coli ESBL is between 65 to 75 years. Recurrent urinary tract infections and previous use of antibiotic treatment are significant risk factors for developing ESBL bacterial infections.